2023
DOI: 10.3390/nu15061471
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMPK Entails the Protective Effect of Royal Jelly against High-Fat-Diet-Induced Hyperglycemia, Hyperlipidemia, and Non-Alcoholic Fatty Liver Disease in Rats

Abstract: This study examined the mechanism underlying the protective effect of royal jelly (RJ) against high-fat-diet (HFD)-mediated non-alcoholic liver disease (NAFLD) in rats. Adult male rats were divided into five groups (n = 8 each): control fed a standard diet, control + RJ (300 mg/kg), HFD, HFD + RJ (300 mg/kg), and HFD + RJ + CC (0.2 mg/kg). The treatment with RJ reduced weight gain, increased fat pads, and attenuated fasting hyperglycemia, hyperinsulinemia, and glucose tolerance in the HFD-fed rats. It also red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…TNF-α is an important cytokine involved in metabolic diseases such as obesity, insulin resistance, hyperlipidemia, and NAFLD [59]. The production of TNF-α in the process of liver injury causes the release of IL-1β and IL-6, which mediates inflammatory response [60].…”
Section: Effect Of Baicalin On Hepatitismentioning
confidence: 99%
“…TNF-α is an important cytokine involved in metabolic diseases such as obesity, insulin resistance, hyperlipidemia, and NAFLD [59]. The production of TNF-α in the process of liver injury causes the release of IL-1β and IL-6, which mediates inflammatory response [60].…”
Section: Effect Of Baicalin On Hepatitismentioning
confidence: 99%
“…Subsequently, an excess of endogenous reactive species such as reactive oxygen species (ROS) and in ammatory signaling cascade in the liver occurs, which leads to hepatocyte injury. A concurrent increase in the secretion of in ammatory cytokines, abnormal liver enzymes, and cellular death is also observed ( Signi cant evidence in animal and preclinical studies has indicated that 5′AMP-activated protein kinase (AMPK) is an effective treatment target for NAFLD (Felemban et al, 2023;Smith et al, 2016). AMPK activation levels are markedly decreased in animals and humans with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK activation levels are markedly decreased in animals and humans with NAFLD. Similarly, activating AMPK through genetic modi cation, exercise, and mitochondria-inhibiting compounds (e.g., metformin) provided protective effects (Fang et al, 2022;Felemban et al, 2023;Strzyz, 2020). AMPK is the main regulator of metabolism, which may regulate food intake, whole-body expenditure, and glucose and lipid hemostasis by affecting various tissues including the hypothalamus, liver, pancreas, muscles, and adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological examination revealed improved liver structure with fewer fat vacuoles in RJ-treated rats. However, when RJ was co-administered with an AMPK inhibitor, compound C (CC), these beneficial effects were attenuated [26].…”
mentioning
confidence: 99%